If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying -14 = 5 + x + -21 Reorder the terms: -14 = 5 + -21 + x Combine like terms: 5 + -21 = -16 -14 = -16 + x Solving -14 = -16 + x Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-1x' to each side of the equation. -14 + -1x = -16 + x + -1x Combine like terms: x + -1x = 0 -14 + -1x = -16 + 0 -14 + -1x = -16 Add '14' to each side of the equation. -14 + 14 + -1x = -16 + 14 Combine like terms: -14 + 14 = 0 0 + -1x = -16 + 14 -1x = -16 + 14 Combine like terms: -16 + 14 = -2 -1x = -2 Divide each side by '-1'. x = 2 Simplifying x = 2
| -5x+7(4-5x)=28-2x | | 23a+17=12(5+4a)-18 | | 13b-76=28 | | 28=16-4m | | -3x+5=-10 | | 7=-9+4x | | -3z-7=23 | | 4n-12=4(2n-3) | | 5t-9=26 | | 4(2x+4)=8(x+2) | | (x+7)(x-2)=36 | | 124-8g=36 | | 4-8x=-6(1+3x) | | 3(4x-3)=6(2x-1) | | 63=3x+9 | | 4+12r=112 | | -11.4x+1.6=-17.6-1.8x | | 4x-3=6x+9 | | 3=2x+13 | | 7x+3=31 | | -8.7x+1.2=-79.1-1.4x | | -7k-33=-3k-7(k+3) | | 3k-5=6 | | 2x+y=26 | | 12-4z=8 | | -(3a+8)=-33+2a | | -8n-5n=-8n-15 | | 12-42=8 | | 6p+6=p+1 | | 13=7+4a | | -6p-4=p+1 | | 46=19+3u |